POTENSI GURU BIDANG STUDI DAN PESERTA DIDIK DALAM MENINGKATKAN MUTU PENDIDIKAN DI SMP NEGERI 1 KARANGANYAR - Indah Kusnul, Khotimah; Yusron, Hanafi (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) STIT Muhammadiyah Tempurejo, Ngawi, Jawa Timur, 2025)
The teacher's ability to deliver appropriate learning is one of the factors that influences the success of increasing the level of education. To ensure students understand the material being taught, teachers must have the ability or skills in KMB (teaching and learning activities). This includes identifying appropriate learning methods. The aim of this research is to: 1) Find out how teachers at SMP Negeri 1 Karanganyar educate their students; 2) Knowing how the students of SMP Negeri 1 Karanganyar respond to their teacher's methods; and 3) Knowing the level of students' understanding of the material studied at SMP Negeri 1 Karanganyar. A qualitative descriptive approach was used in this research. Documentation, events and informants are sources of research data. Meanwhile, data collection. The results of this research are 1) The method used in teaching and learning at SMP Negeri 1 Karanganyar adapts to the existing curriculum, the method uses varied methods that combine methods so that the learning taught is innovative and afficient, 2) Students responses to the teachers teaching method using this method is enough to make them happy, because the material taught is easy to understand, 3) The level of students understanding can be seen from changes in attitudes, assignment scores and test scores.